Evaluasi Keterlambatan Proyek Pembangunan Jembatan Gantung Bangun Jawa I Kabupaten Serdang Bedagai - Br. Brahmana, Ebigael Jovanka; Ardan, Melloukey; Irwan, H. (Universitas Medan Area, 2024)
Delays in construction projects often result in losses for construction actors, and can be caused by internal, external, and other factors such as natural, management, material, and environmental disasters. Research was conducted on the Java I Construction Suspension Bridge project, Serdang Bedagai Regency to evaluate delays in terms of cost and time. The goal is to evaluate the schedule of the project plan and implementation and find out the cause. Evaluation using the Earned Value Management method shows that project implementation tends to be slow, but costs are still below budget with an estimated Rp. 2,454,274,500,- and 36 weeks. Delays are caused by the engineering justification process, late delivery of bridge trusses, and instability of service provider cash flow. This research is expected to provide a reference for construction actors to anticipate delays in other projects.